Investigations of potential pharmaceutical biofillers based on pregelatinized starch-reinforced with pine-extracted cellulose - Albarahmieh, E.; Tabbalat, S.; Muhaisen, R. (Jordan Journal of Pharmaceutical Sciences, 2023)
Starch unique physical properties and abundance makes it an ideal candidate as diluent or filler in tablets. Therefore, this work aims to produce a modified starch known as ‘pregelatinized’ with the support of renewable cellulosic wood and characterize its properties in an effort to improve its application versatility that notably appeal to the pharmaceutical industry for greener and more sustainable excipients.